2018
DOI: 10.1097/md.0000000000013708
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac tamponade as the initial symptom due to systemic lupus erythematosus in a young man

Abstract: Rationale:Systemic lupus erythematosus (SLE) is a connective tissue disease that has many clinical manifestations. However, cardiac tamponade has been rarely reported especially as an initial presenting feature of systemic lupus erythematosus. Herein, we describe a case of cardiac tamponade as the first presentation of systemic lupus erythematosus in a male and presented the course of diagnosis and treatment of this patient.Patient concerns:A 32-year-old male patient developed a rapid progression of pericardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Studies have reported the average interval time from initial symptom onset to formal diagnosis ranging from six months to four years [6]. However, sparse reports of cardiac tamponade as the initial presentation of SLE have been reported [4, 7-13]. This current case differs from these previously cited cases, including patient sex and age, volume and rapidity of pericardial effusion, and subsequent development of tamponade development.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Studies have reported the average interval time from initial symptom onset to formal diagnosis ranging from six months to four years [6]. However, sparse reports of cardiac tamponade as the initial presentation of SLE have been reported [4, 7-13]. This current case differs from these previously cited cases, including patient sex and age, volume and rapidity of pericardial effusion, and subsequent development of tamponade development.…”
Section: Discussionmentioning
confidence: 74%
“…Our patient’s age of presentation is modestly outside the mean age range of both male symptom onset and diagnosis in SLE (26 - 38.4 years and 26 - 55 years, respectively), adding to the case’s novelty [14]. Only two of the reported cases above had affected patients of the male sex, and the ages of those male patients, 32 and 61 years of age, are significantly older than that of our patient [7, 13]. While even small volume pericardial effusions may lead to tamponade, there is a correlation of larger volumes being predictive of this sequela [15].…”
Section: Discussionmentioning
confidence: 83%
“…The clinical manifestations of tamponade are brought on by a decrease in cardiac output and systemic venous congestion. Cardiac tamponade as the first sign of SLE is very rare and only limited to case reports and series [6,10,13,14]. Typical symptoms and signs include dyspnea, orthopnea, chest pain, pulsus paradoxus, jugular venous distension, and hypotension [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac involvement is common and can be found in more than half of SLE patients [3,4]. Although pericarditis and pericardial effusion are the most common cardiac manifestations, cardiac tamponade, especially as the initial manifestation of the disease, is extremely uncommon [5,6]. In this case report, we describe a 38-year-old Nigerian woman whose initial manifestation of SLE was cardiac tamponade.…”
Section: Introductionmentioning
confidence: 92%
“…Nonsteroidal anti-inflammatory medicines (NSAIDs), corticosteroids, immunosuppressive medications, and biological agents may be used to treat lupus, depending on the symptoms, findings of blood tests, and the specific organs affected. With the right care, most lupus sufferers may anticipate a normal lifetime, but many may endure some degree of impairment [8]. More serious health issues associated with lupus, such neurological issues and kidney damage, need for aggressive therapy.…”
Section: Introductionmentioning
confidence: 99%